Iconoclasm of normative structures: exploring queer ageing in “Kaathal: The core” by Jeo Baby - Preethika Shree, A. C.; Chithra, G. K. (Frontiers in Sociology, 2025)
IntroductionThis research critically examined the portrayal of older gay men through an iconoclastic perspective in the Malayalam film “Kaathal: The core,” directed by Jeo Baby, focusing on the intersecting identities of age, marriage, and homosexuality as depicted in the film, further exploring how these overlapping facets shape the characters’ lives and experiences.MethodologyA qualitative research approach was employed to examine the representation of older gay men in the film. The study focused on narrative analysis of key scenes, dialogues, character portrayals, and cinematic elements to explore how the intersection of age, sexuality, and cultural norms is depicted.ResultsThe film narrative explored the challenging circumstances faced by the older gay characters, Mathew Devasy and Thankan, within a heteronormative cultural framework, particularly as of those who stay mute on their identity, remaining isolated and vulnerable. The research discloses the hetero character Omana’s display of significant agency, challenging traditional views on family and belonging.DiscussionThe film critiques the rigid heteronormative framework of traditional family structures, offering alternative perspectives through non-traditional kinship and support systems. By addressing the intersection of age, sexuality, and cultural norms, this research emphasizes the importance of expanding queer representation to include diverse identities and life stages, paving the way for more inclusive cinematic discourses.